Tacit Knowledge Sharing in Organizational Knowledge Dynamics - Bratianu, C.; Orzea, I. (Journal of Knowledge Management Practice, 2010)
The purpose of this paper is to analyze knowledge sharing as a core component of the organizational knowledge dynamics, and to present some specific organizational barriers in the Romanian business environment. Tacit knowledge represents the direct result of the interaction between the individual and the external environment. It is the knowledge acquired through direct experience, comprising also feelings, intuitions, beliefs and cultural values. Tacit knowledge has become the central piece of attention of knowledge management, since managers recognized that it is a core component of the organizational knowledge dynamics. Tacit knowledge sharing contributes directly to enhancing knowledge creation and to obtaining a competitive advantage in the business environment. However, tacit knowledge sharing may have many organizational barriers, especially in those new economies developed in the former socialist countries. We based our research on the Romanian companies, since our country suffered from a dictatorial socialism regime. Our research demonstrates that the organizational culture developed during the socialism regime has been based on fear, individual control, mistrust and a dictatorial managerial style. People were always controlled and kept under close observation by the state, this inducing a constant tension in them and fear of expressing ones beliefs. Having in mind the background of the Romanian’s culture and the requirements of a successful process of knowledge sharing our research aims at identifying the barriers that employees are faced with in sharing their knowledge and propose solutions to overcome these and improve the process of knowledge sharing within the Romanian business environment.